KEARIFAN BUDAYA PADA CERITA RAKYAT MASYARAKAT CILACAP DALAM PERSPEKTIF PARIWISATA KABUPATEN CILACAP - Triningsih Triningsih (CARAKA, 2015)
Folklore was born as the product of the culture in society; it can be in the form of myth, legend, or tale. In folklore, there are cultural value and wisdom that can be used as the guidance of life for the society, such as, democratic value, the value of hard-working, the value of honesty, moral, and love to their country. Those values lie in Cilacap’s folklore. Their existence takes part in the increase of tourism visit, which, at the end, hopefully, can increase the society’s economic level.